Do late bloomers exist among adjudicated youth?: examining parental factors and ADHD symptomatology as contributors to protective bud and bloom effects - Wojciechowski, Thomas W. (Journal of developmental and life-course criminology, 2023)
Prior life-course research has indicated support for the existence of a late bloomer offending trajectory characterized by minimal offending risk during adolescence and sharp acceleration of offending in adulthood. While some research has sought to understand drivers of such patterns of offending, there remain gaps in the literature pertaining to social and psychiatric drivers of this offending pattern. Further, research focused on understanding these developmental processes among youth offender populations is limited as well. This study sought to understand the relevance of attention-deficit hyperactivity disorder (ADHD) symptomatology and parental factors for understanding late bloomer offending among a sample of justice-involved youth. The Pathways to Desistance data were utilized in analyses. Group-based trajectory modeling was used to identify latent patterns of offending, and t tests were used to examine group differences. A late bloomer offending trajectory was identified in the data. Results further indicated that certain aspects of ADHD symptomatology differentiated late bloomers from low-frequency offenders and that parental socioeconomic status and parental monitoring played limited roles in delineating late bloomers from low-frequency offenders and chronic offenders. These results indicate the need for identification of social and psychiatric factors among youth involved with the justice system. Doing so may allow for early intervention that may mitigate risk for acceleration in offending later in life among a subset of these youth.